The Role of Accounting in Performance Evaluation to Optimize Organizational Performance - Siti Alya Noviani; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2025)
This study aims to determine the role of accounting in performance evaluation to optimize organizational performance. This study uses a literature review method by collecting and analyzing various sources from the Google Scholar database related to the role of accounting in evaluating and optimizing organizational performance. The results of the Literature Study show that the implementation of proper accounting and systematic performance evaluation make a significant contribution to the success of the company's operations. An effective AIS not only improves accuracy in financial management but also improves employee performance by providing relevant information for strategic decision making enabling companies to develop effective programs and address internal problems.